Pengaruh pijat punggung pada lansia dengan gangguan kualitas tidur - Sastria Handayani; Elliya, Rahma; Furqoni, Prima Dian (JOURNAL OF Mental Health Concerns, 2024)
Abstract   Background: The elderly are a group of human ages that are in the final stages of life. The elderly experience a process called aging. These changes generally lead to a decline in physical and mental health. One of the deterioration of the elderly that can affect the physical and psychological aspects of the elderly is the quality of sleep. Massage therapy helps cure various physical ailments. The right massage can address a variety of health issues. Massage not only cures physical ailments, but it also calms the mind, reduces stress, and makes you feel more comfortable. It can also trigger the release of endorphins, brain chemicals that create feelings of comfort and improve sleep quality. Purpose: To carry out nursing care on the influence of back massage therapy to overcome quality disorders in elderly patients. pretest-posttest design without a control group, and the design of this study is included in the pre-experimental study. The nature of nursing research in this study is a pseudo-experiment or quasi-experiment and aims to reveal the influence of adaptive manipulation on respondents. Results: Based on the results of the case study that has been carried out, the results were obtained that both respondents had good sleep quality with a score of 5 after being given a back massage. After applying a back massage for 3 days before going to bed with a duration of 10 minutes, Mrs. M had good sleep quality with a sleep quality score of 5 and Mrs. N had good sleep quality with a sleep quality score of 5. Conclusion: Nursing care carried out for 5 days on both Mrs. M and Mrs. N clients there were results of a decrease in scores before and after the treatment of orthogonal massage therapy for 3 days where both respondents had good quality with a score of < 5 after being given a back massage for 3 days before going to bed with a duration of 10 minutes